Insecticidal activity of the essential oil of Lippia alba (Mill.) N. E. Brown on Tribolium castaneum Herbst. in stored wheat grains - Ringuelet, Jorge; Ocampo, Rafael; Henning, Cynthia; Padín, Susana; Urrutia, María Inés; Dal Bello, Gustavo (Revista Brasileira de Agroecologia, 2014)
Tribolium castaneum (Coleoptera: Tenebrionidae) is an insect pest of stored grain, very destructive and highly resistant to synthetic pesticides. Therefore, the chemical control of this pest is performed with high concentrations of insecticides which increase environmental contamination as well as the risks to human health. Current trends in integrated pest management are focused on the use of biological pesticides such as plant extracts, which do not generate resistance and are of low toxicity. In that sense, the objective of the present research was to study the repellent and insecticidal activity of the essential oil of Lippia alba (Verbenaceae) chemotype carvone-limonene on adults of T. castaneum, in wheat grain. The repellency was evaluated using an olfactometer with a concentration of essential oil of 52 μL L-1air, at 2 and 24 h, and 7, 14 and 21 days. The insecticide effect was determined by the spraying technique and by the impregnation of paper with the essential oil at concentrations of 131, 263 and 526 μL L-1 air, recording mortalities at 24 hand 7 days post treatment. Significant to highly significant differences were observed for repellency respect to control in all the analyzed periods. In relation to mortality, comparing the techniques of application of essential oil using the highest concentration, at 24h significant differences in favor of spraying were found, while at 7 days, there were no differences between both methods. It is concluded that the essential oil of L. alba would represent an environmentally friendly alternative to prevent and control the attack of adults of T. castaneum in stored grains.